Geochemically anomalous olivine-poor nephelinite of Rip Hill, Czech Republic - Ulrych,J.; Pivec,E.; Langrova,A.; Jelinek,E.; Arva-Sos,E.; Hohndorf,A.; Bendl,J.; Randa,Z. (Journal of the Czech Geological Society, 1998)
Sodalite olivine-poor nephelinite of Rip Hill substantially differs both from olivine nephelinite and olivine-free nephelinite of the Cenozoic volcanic province of the Bohemian Massif. Rip Hill represents an erosion-resistant neck 25.6 Ma in age located in the Tepla-Barrandian terrane block in contrast to the Ceske stredohori Mts. volcanic complex in the Saxothuringian terrane. The very low Mg-value (48.5), low contents of compatible elements as Cr (79 ppm), Ni (31), Co (32), Sc (21) and lack of mantle-type xenoliths gives evidence of differentiation of primary mantle magma. Anomalous enrichment in incompatible elements particularly in ∑REE (650 ppm), U (3.6), Th (15.6), Nb (154), Ta (12.1), is associated with late magmatic crystallization (mostly of apatite, Ti-magnetite ± hauyne). 87Sr/86Sr (0.7036-0.7038) and 143Nd/144Nd (0.51278) ratios of the olivine-poor nephelinite are consistent with HIMU OIB from a sublithospheric source; εtNd (+3.4) value implies an depleted mantle source. Olivine-poor nephelinite could be derived from carbonated nephelinite magma with high CO2/H2O + CO2 volatile fraction resulting in high viscosity and thus stopping of magma associated with differentiation and contamination in crustal reservoir during its ascent to the surface. Such magma could be associated with high explosive pyroclast-rich volcano of maar or stratovolcano type. The olivine-poor nephelinite of Rip Hill reveals common features in mineral paragenesis and chemical composition of minerals such as clinopyroxene, (Mg, Al, Ti)-magnetite, barite, ankerite with carbonate-bearing alkaline ultramafic lamprophyres in the vicinity. This fact suggests their mutual genetic association within the Rip Hill volcanic centre.
Keywords: Bohemian Massif; Rip Hill; olivine-poor nephelinite; geochemistry; age; Sr; Nd isotopes